Online Training and Contests for Informatics Contestants of Secondary School Age - NÉMETH, N; ZSAKÓ, László (Journal of Education, Technology and Computer Science, 2015)
If you prepare students for programming contests carefully selected andwidely available online training and contests offer help and diversity. If youteach about testing programs you have to know which sites offer downloadabletests or feedback with detailed test cases. If you want to make series of tasks forpracticing you have to know which sites offer you categorized tasks of the appropriatelevel. In order to be able to choose from the available materials weneed to categorize them. The previously defined and used criteria need somesupplement criteria for better and sophisticated use of categorization from theteacher’s point of view. Online resources can be classified in general: what programminglanguages can be used, how often the contests are organized, in whichlanguages they can be accessed, what types of problems a website deals with andat what level, what prior knowledge is required. We can group sites according towhether they help teachers to set tasks for their students, or get ideas for solutionsor see the results of their students. Online contests can also be categorizedregarding whether students can see each other's solutions. The aim of this paperis to supplement the categorization and describe some major portals according tothe previously defined and supplemented criteria.